Abundance and Symbiotic Rhizobia Colonizing Soybean (Glycine max) in Soils of Kakamega County, Western Kenya - Samuel Mulama; Rose Onamu; Fredrick Odongo; John Muoma (International Journal of Agronomy)
Identification of effective indigenous rhizobia strain nodulating soybean (Glycine max) was conducted in Kakamega County, Western Kenya. This study was carried out to establish the abundance and symbiotic efficiency of native rhizobia strains in soil samples collected from 12 sites in four agroecological zones within the region. The MPN enumeration technique was used to estimate the indigenous rhizobia numbers and showed that 54% of the sampled sites had high abundance. Rhizobia number in the soil collected from the six regions varied from 2.5 × 102 to 3.12 × 103 cells·g− soil. Thirty isolates from the soil collected in the four regions were tested for efficiency using soybean as the trap plant in Leonard jars containing sterilized vermiculite irrigated with nitrogen-free media. Determination of the relationship between rhizobial abundance and symbiotic efficiency with respect to the soil chemical conditions was performed using ANOVA, and the means were compared using Tukey’s honest significant difference test. Inoculation with bacterial isolates significantly (P<0.05) increased the nodule number and shoot dry weight, while weight of the seeds showed variations across the groups. The soil pH across the 4 regions ranged between 5.41 and 6.52.